Peningkatan Kemampuan Literasi Digital Melalui Bina Kreativitas Smart Vloger Bagi Pemuda Karang Taruna Di Desa Pameuntasan Kecamatan Kutawaringin Kabupaten Bandung - Mariane, Ine; Indrianie, Mona (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
In today's digital era, digital literacy skills are a primary need for the younger generation, including in rural areas. However, youth from the Karang Taruna (Youth Organization) in Pameuntasan Village still tend to be passive consumers of social media, failing to utilize it creatively and productively. Meanwhile, the village's potential—including culture, tourism, and social activities—has not been optimally utilized as digital content. Therefore, a program is needed to encourage youth to become "Smart Vloggers," namely creators of intelligent, positive, and locally-based content. The problems faced by partners include low critical digital literacy among village youth, a lack of knowledge and skills in creating creative and informative vlog content, and the lack of digital media to promote village potential. The targeted outputs of the solution are increased knowledge, understanding, and skills about the importance of digital literacy through Smart Vlogger Creativity Development for Karangtaruna (Karta) youth in Pameuntasan Village, Kutawaringin District, Bandung Regency, and strengthening community social institutions to create an independent and productive generation. The results of PKM, Pemuda Karta and Kompepar in Pameuntasan Village, Kutawaringin District, Bandung Regency are expected to be able to know, understand, and use digital media literacy skills safely in updating writing on the platforms they create. Able to become Smart Vloggers to strengthen community social institutions in promoting the potential of their villages.